Late Onset Alzheimer Dementia in Patients with Genotype E3/E4: A Case Report - Laksmidewi, Anak Agung Ayu Putri; Vania Rau, Chiquita Putri (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Dementia is one of the leading causes of disability and dependence in elderly worldwide. Epidemiological statistics indicate that data show that at about 60–80%, Alzheimer’s is the most common type of dementia. Alzheimer’s is also the third-most prominent cause of death in elderly. CASE REPORT: A 72-years-old male patient, complained by the family often forgets about things that have just been done for 3 years ago. According to the family, patient also often discussing the same things repeatedly. Patients tend not to have the initiative to start his daily activities. The family admitted that patient also became often angry and felt suspicious for the last 2 years. From the mini mental state examination showed disturbances in time orientation and recall; from Montreal Cognitive Assessment Ina found disturbances in visuospatial, fluency, abstraction, delayed memory, and time orientation; accompanied by activities of daily living (ADL) and instrumental ADL disorders. Patient also performed a molecular examination of the apolipoprotein E (APOE) genotype and the genotype E3/E4 was detected. CONCLUSION: The function of the APOE gene, in particular APOE4, is the most emphasized genetic relationship in late onset Alzheimer’s disease. It is proposed that blocking the action of APOE4 can delay or stop Alzheimer’s disease progression.